A DNA vaccine for Crimean-Congo hemorrhagic fever protects against disease and death in two lethal mouse models. - Aura R Garrison; Charles J Shoemaker; Joseph W Golden; Collin J Fitzpatrick; John J Suschak; Michelle J Richards; Catherine V Badger; Carolyn M Six; Jacqueline D Martin; Drew Hannaman; Marko Zivcec; Eric Bergeron; et al. (Public Library of Science (PLoS), 2017)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne virus capable of causing a severe hemorrhagic fever disease in humans. There are currently no licensed vaccines to prevent CCHFV-associated disease. We developed a DNA vaccine expressing the M-segment glycoprotein precursor gene of CCHFV and assessed its immunogenicity and protective efficacy in two lethal mouse models of disease: type I interferon receptor knockout (IFNAR-/-) mice; and a novel transiently immune suppressed (IS) mouse model. Vaccination of mice by muscle electroporation of the M-segment DNA vaccine elicited strong antigen-specific humoral immune responses with neutralizing titers after three vaccinations in both IFNAR-/- and IS mouse models. To compare the protective efficacy of the vaccine in the two models, groups of vaccinated mice (7-10 per group) were intraperitoneally (IP) challenged with a lethal dose of CCHFV strain IbAr 10200. Weight loss was markedly reduced in CCHFV DNA-vaccinated mice as compared to controls. Furthermore, whereas all vector-control vaccinated mice succumbed to disease by day 5, the DNA vaccine protected >60% of the animals from lethal disease. Mice from both models developed comparable levels of antibodies, but the IS mice had a more balanced Th1/Th2 response to vaccination. There were no statistical differences in the protective efficacies of the vaccine in the two models. Our results provide the first comparison of these two mouse models for assessing a vaccine against CCHFV and offer supportive data indicating that a DNA vaccine expressing the glycoprotein genes of CCHFV elicits protective immunity against CCHFV.